2000
DOI: 10.2214/ajr.174.2.1740463
|View full text |Cite
|
Sign up to set email alerts
|

CT Features of Metastatic Linitis Plastica to the Rectum in Patients with Peritoneal Carcinomatosis

Abstract: Metastatic linitis plastica to the rectum should be considered when CT shows a long segment of circumferential rectal wall thickening, especially in patients with peritoneal carcinomatosis from gastric cancer. In such patients, CT helps avoid unnecessary extensive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 10 publications
7
32
0
1
Order By: Relevance
“…Ha et al [19] reported that when the tumour infiltrates all layers, it expands the mucosa, submucosa and serosa rather than the muscularis propria owing to the more tightly packed muscle cells of the latter tissue. Therefore, the muscularis propria is the least thickened hyperattenuating layer in scirrhous metastasis; Gollub et al [14] termed this feature the malignant target sign.…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al [19] reported that when the tumour infiltrates all layers, it expands the mucosa, submucosa and serosa rather than the muscularis propria owing to the more tightly packed muscle cells of the latter tissue. Therefore, the muscularis propria is the least thickened hyperattenuating layer in scirrhous metastasis; Gollub et al [14] termed this feature the malignant target sign.…”
Section: Discussionmentioning
confidence: 99%
“…La biopsia con Trucut guiada por ecoendoscopia es un método seguro para obtener muestras de mayor tamaño, pudiendo disminuir el número de pases comparado con la PAAF 9,10 . Realizar un diagnóstico citohistológico correcto es esencial para poder seleccionar las intervenciones terapéuticas más adecuadas El pronóstico de la linitis rectal secundaria es ominoso, puesto que cuando se alcanza el diagnóstico suele ser en fases muy tardías de la enfermedad y sin tratamiento efectivo, existiendo con frecuencia metástasis ganglionares y carcinomatosis peritoneal hasta en un 50-80% de los casos en el momento del diagnóstico 11,12 . En nuestros pacientes la supervivencia desde el diagnóstico fue corta (4 meses en el primer caso y menor de un mes en el segundo).…”
Section: Discussionunclassified
“…2 Histologically, linitis plastica exhibits a marked fibrotic response within the bowel wall and frequently a relative paucity of tumor cells. 1,2 The condition may involve all layers of the wall or may be confined to the submucosa. 4 These features contribute to the difficulty in establishing a diagnosis from an endoscopic biopsy, which, if superficial, may only sample the mucosa.…”
Section: Discussionmentioning
confidence: 99%